Biography of Jamal al-din Mahmoud Qunawī and His Works and His Mukhtasar Named Muntakhab Waqfay Hilāl wa’l-Khassāf - Yasin Erden (İslam Tetkikleri Dergisi)
In his pamphlet on istibdāl or the act of giving, Qinalizāde ‘Ali Efendi, qualifies Hilāl and Khassāf as “the shining stars in the sky of the waqf [law] and the pillars that the roof of waqf [law] is looming over them.” Due to their importance, the books written by Hilāl and Khassāf, who lived in the formative period of Hanafī fiqh, began to be abridged in the following periods. Nāsıhī, who first served as a qādī and a qādī al-qudāt in the Ghaznavid state, wrote a mukhtasar on the Hilal and Khassāf books. Jamal al-din Mahmoud Qunawī, one of the Mamlūk qādī al-qudāt, who died about three and a half centuries after Nāsıhī, also wrote a similar mukhtasar onthese works. Finally, the Hanafī faqīh from Damascus, Burhānaddīn Tarablosī, wrote a mukhtasar named al-Is’āf fî ahkām al-awqāf. As a result of the recent examinations of older library collections, it is believed that the mukhtasar of Jamal al-din Mahmoud Qunawī may be waiting for discovery as a manuscript in the libraries. This study presents valuable information about the life and works of Jamal al-din Mahmoud Qunawī, known as “Ibnü’s-Sirāj”. The paper also provides the critical edition of the mukhtasar called Muntakhab Waqfay Hilāl walKhassāf, which Qunawī wrote regarding the field of Hanafī waqf law. The sources claim that Qunawī served as a qādī al-qudāt of Damascus in the Mamlūk state and penned works in hadīth, tafsīr, ʿaqāʾid in addition to his more numerous works in the field of fiqh.